COVID-19 Lockdown and Social Capital Changes Among Youths in China - Miyang Luo; Dong Zhang; Pengyue Shen; Yun Yin; Shujuan Yang; Peng Jia (Kerman University of Medical Sciences, 2022)
Social capital refers to the effective functioning of social groups through networks of relationships. The lockdown measures due to coronavirus disease 2019 (COVID-19) may change the social capital among youths. This study aimed to evaluate changes in social capital before and during COVID-19 lockdown among Chinese youths. It was based on the online COVID-19 Impact on Lifestyle Change Survey (COINLICS) conducted among 10 540 youths at three educational levels, including high/vocational school, undergraduate, and graduate, before and during COVID-19 lockdown. Measures of perceptions of social capital were adapted from a validated Chinese version of Health-related Social Capital Measurement based on youths' characteristics of living and studying environment. Social capital was measured at four dimensions, including individual social capital (ISC), family social capital (FSC), community social capital (CSC), and society social capital (SSC). Overall, compared to before lockdown, ISC and CSC scores decreased, while FSC and SSC scores increased during lockdown. When stratified by educational levels, the trends for each dimension of social capital were consistent with the overall population. There were 43.9%, 5.7%, 32.1%, and 3.7% of the participants showing decreased scores during lockdown for ISC, FSC, CSC, and SSC, respectively, while 7.2%, 24.0%, 15.3%, and 10.7% of participants showed increased scores for ISC, FSC, CSC, and SSC, respectively. Our timely, largescale study showed decreased social capital in individual and community dimensions and increased social capital in family and society dimensions during lockdown.